An investigation into the factors enabling and constraining the implementation of Recognition of Prior Learning (RPL): a case of the public service sector in two South African provinces - Tywabi, Siviwe (My University, 2020)
The South African economy is in need of skilled workers, yet many competent employees are underutilised and disadvantaged owing to them not being able to produce evidence of their competence in the form of academic qualifications. The National Development Plan (NDP) calls for the building of a “capable state”. According to the National Planning Commission (NPC) the state is capable to the extent “that it has the capacity to formulate and implement policies that serve the national interest” (NPC, 2012). A capable and developmental state is one that has the means to identify and deal with the causes of poverty and inequality in South Africa. The Recognition of Prior Learning (RPL) in South Africa must build on the commitment of all role-players to remove barriers to learning and develop a visible, usable and credible system as an effective and creative vehicle for lifelong learning. This research report is an interpretive study which is dependent on the views of key persons in understanding the factors enabling and constraining the implementation of RPL for credit in the public service sector. A case study of two South African provincial government department who have implemented RPL. The RPL was implemented against the Public Sector Education and Training Authority (PSETA) registered workplace-based learning National Certificate in Public Administration qualification were investigated. Hence this study does not necessarily present a comprehensive account of the implementation of RPL in the two provinces that were studied. The research study seeks to describe the experiences and to link such experiences to the literature that describes workplace/ experiential learning in relation to the implementation of RPL. This study aims to establish implementation practices of RPL for credit in the public service sector and forge a deeper understanding of the factor that contribute to the successful implementation of RPL for credit. It also aims to identify barriers and constraints in the implementation of RPL for credit. The findings of the research revealed that the participants who are employees in the two provincial departments sampled derived a range of emancipatory benefits from the RPL programme. The RPL programme has enabled previously disadvantaged employees to obtain credits towards a full qualification registered on the National Qualifications Framework (NQF). This research study is conceptualised against the background of Kolb’s Experiential Learning Theory. This is a conceptual framework which has widely contributed to understanding adult and professional learning. The analysis of the study is then brought together by Cooper and Ralphs’ framework that considers RPL as a specialised pedagogical practice that cannot be theorised as a conventional form of transmission, acquisition and assessment of knowledge from a single body or source
A research report submitted in fulfilment of the Masters’ Degree in Education in the Faculty of Humanities (School of Education), University of the Witwatersrand, 2020
Keywords: College credits; Education, Higher--South Africa